ІNWAZYJNE GATUNKI FLORY MIASTA CZERNIHÓW (UKRAINA) - Лукаш, Олександр; Мірошник, Ірина; Бойко, Володимир (Biota. Human. Technology, 2022)
ABSTRACT Purpose: to do the analysis of the invasive species of the Chernihiv city flora (Ukraine). Methodology. The invasive species of Chernihiv were selected on the basis of the “List of the alien species that are proposed to be considered as dangerous invasive ones on the territory of Ukraine and included in the “black list””. The analysis of the geographic origin of the invasive species was made on the basis of the arealogical data on the synanthropic species given in domestic and foreign works. 335 geobotanical descriptions were made to determine the ecological and cenotic range of the invasive species in the city of Chernihiv. The syntaxon identification was made on the basis of the ecological and floristic classification. Scientific novelty. 34 invasive species were found in the adventitious fraction of the Chernihiv city flora, their phytocenotic and geographical analysis was made. It is established that the natural conditions of the study area and the factors of anthropogenic impact on the environment first of all contribute to the spread of the kenophytes of the North American origin. It was proved that the active spread of Ambrosia artemisiifolia quarantine weed over the last decade had been causing a particular danger. Conclusions. In Chernihiv, we observe the expansion of the invasive species that came to the region 120-50 years ago (Acer negundo, Amorpha fruticosa, Cyclachaena xanthiifolia, Impatiens parviflora, Xanthium albinum, Echinocystis lobata, etc.), and also the alien species (Ambrosia artemisiifolia, Bidens frondosa, Solidago canadensis, Heracleum mantegazzianum, Reynoutria japonica, Impatiens glandulifera Royle, Helianthus subcanescens). The hydrophilic species such as Bidens frondosa, Echinocystis lobata and Impatiens grandulifera have the largest phytocenotic spectrum in the natural plant communities. The range of the most vulnerable to the invasive plant communities (in order of decreasing their stability) in Chernihiv is the following: moderately moist meadow communities of the Arrhenatherion and Agropyro-Rumicion crispi alliances – the Salicion albae forested and shrubby floodplain communities – the Alnion incanae not swampy forests, the Dicrano-Pinion pine forests – the Epilobion angustifoliae dry outskirts communities. The synanthropic communities affected by the invasive species belong to 17 alliances. Acer negundo, Ambrosia artemisiifolia, Echinocystis lobata, Helianthus subcanescens, Heracleum mantegazzianum, Solidago canadensis, Robinia pseudoacacia, the species of the Amaranthus, Cannabis sativa, Conyza canadensis, Galinsoga parviflora, G. urticifolia, Impatiens parviflora, Phalacroloma annuum, Phalacroloma septentrionale kind have the largest phytocenotic spectrum and frequency of the occurrence in these synanthropic plant communities. Further rooting of kenophytes in the invasive natural plant communities due to the low competitiveness of the native flora species may lead to a loss of the representativeness of the natural florocenocomplexes of the Chernihiv outskirts. АНОТАЦІЯ Мета роботи: здійснити аналіз інвазійних видів флори міста Чернігів (Україна). Методологія. Інвазійні види м. Чернігова виділені на основі «Переліку чужинних видів, які пропонується визнати небезпечними інвазійними на території України та включити до “чорного списку”». Аналіз географічного походження інвазійних видів здійснено на основі ареалогічних даних про синантропні види, наведених у вітчизняних та зарубіжних працях. Для визначення еколого-ценотичної приуроченості інвазійних видів у межах м. Чернігова виконано 335 геоботанічних описів. Ідентифікація синтаксонів проводилася на основі еколого-флористичної класифікації. Наукова новизна. У адвентивній фракції флори м. Чернігова виявлено 34 інвазійні види, проведено їх фітоцентичний та географічний аналіз. Встановлено, що природні умови регіону досліджень та чинники антропогенного впливу на довкілля у першу чергу сприяють поширенню кенофітів північноамериканського походження. Доведено, що особливу небезпеку становить активне поширення протягом останнього десятиріччя карантинного бур’яну Ambrosia artemisiifolia. Висновки. У м. Чернігові спостерігаємо експансію інвазійних видів, які потрапили у регіон 120–50 років тому (Acer negundo, Amorpha fruticosa, Cyclachaena xanthiifolia, Impatiens parviflora, Xanthium albinum, Echinocystis lobata тощо), а й новітніх чужорідних видів (Ambrosia artemisiifolia, Bidens frondosa, Solidago canadensis, Heracleum mantegazzianum, Reynoutria japonica, Impatiens glandulifera Royle, Helianthus subcanescens). Найбільший фітоценотичний спектр у природних рослинних угрупованнях мають гігрофільні види Bidens frondosa, Echinocystis lobata та Impatiens grandulifera. Ряд найбільш вразливих щодо інвазійних видів рослинних угруповань (у порядку зменшення стійкості) в м. Чернігові є таким: помірно зволожені лучні угруповання союзів Arrhenatherion та Agropyro-Rumicion crispi – лісові та чагарникові заплавні угруповання Salicion albae – гігрофільні незаболочені ліси Alnion incanae, соснові ліси Dicrano-Pinion – сухі узлісні угруповання Epilobion angustifoliae. Синантропні угруповання, вражені інвазійними видами належать до 17 союзів. Найбільші фітоценотичний спектр і частоту трапляння у цих синантропних рослинних угрупованнях мають Acer negundo, Ambrosia artemisiifolia, Echinocystis lobata, Helianthus subcanescens, Heracleum mantegazzianum, Solidago canadensis, Robinia pseudoacacia, види роду Amaranthus, Cannabis sativa, Conyza canadensis, Galinsoga parviflora, G. urticifolia, Impatiens parviflora, Phalacroloma annuum, Phalacroloma septentrionale. Подальше укорінення кенофітів у інвазіабельні природні рослинні угруповання завдяки низькій конкурентноздатності видів місцевої флори може призвести до втрати репрезентативності природних флороценокомплексів околиць Чернігова.